Elements of Nature in D. N. Mamin-Sibiryak’s Novel Bread - Soboleva, Larisa (Quaestio Rossica, 2015)
The article considers imagery connected to the elements of nature in the novel Bread (1895) from the Urals cycle by the known Russian writer Dmitry Mamin-Sibiryak; it explores the importance of the images of water, earth, and fire for the realization of the novel’s main idea. The novel is based on the events preceding and following the great hunger of the 1891–1892 that had affected even the most fertile lands of Russia and touched upon the Trans-Urals. We argue that the writer sees the causes for this catastrophe not as much in the forces of nature, as in the general indifference of the people, their vane ambitions, absence of mercy, irresponsibility of the officials, and merchants’ own adventurism. The novel’s main heroes give in without exception to the temptation of easy life and fast enrichment. Loss of immunity to evil and reluctance to consider the consequences of one’s own actions leads to amorality in traditionally agricultural regions. Fertile land, once utopianly beautiful, turns into cold desert towards the end of the novel. The force of life transforms into deadly threat. Klyuchevaya river that was lavishly giving away its waters, serving as the main artery for the vast region, turns into a grave for the main hero, Galaction Kolobov. The fire rages in the city, destroying it like a divine power that is punishing sinners. The elements, being an integral part of nature, therefore attain utterly symbolic meaning in the novel, revealing awful consequences of the human moral fail to the reader. The author uses those interpretations of the imagery that stem from the Biblical and popular Christian understanding. Introducing elements of nature endows the novel with a universal dimension; thus small town events become tropes of the all-human tragedy resulting from the loss of true life values. Mamin-Sibiryak painfully anticipates the forthcoming catastrophes of the 20th century; analyzing in his novel the deadly results of the recent events, he warns the reader of a possibility for yet deeper crisis, leaving them at the crossroads of the diverse possible ways for their Motherland.